Expression levels of blood platelet and C-reactive protein in patients with severely pneumonic and their predictive values for efficacy - Li, Lihong; Ren, Baozhong; Guo, Jian; Zhang, Zhicang; Cai, Yuxing; Yin, Jie (Cellular and Molecular Biology, 2020)
This paper aims to detect the expression levels of blood platelet (PLT) and C-reactive protein (CRP) in severely pneumonic patients and analyze their correlation. For this purpose, eighty-one severely pneumonic patients were retrospectively selected as an observation group and 106 healthy people as a control group. Pretreatment and post-treatment expression levels of PLT and CRP, their predictive values for efficacy, and correlation of PLT, CRP, and PSI scores in observation group after treatment were analyzed. Before treatment, the expression level of PLT in the observation group was higher than the control group (P< 0.05). In the observation group, the expression level of PLT after treatment was significantly lower than that before treatment (P< 0.05). Before treatment, the expression level of CRP in the observation group was higher than the control group (P< 0.05). In the observation group 1) the pretreatment PLT expression level was higher than that in the control group; 2) the post-treatment PLT expression level was significantly lower than that in the pretreatment one; 3) the pretreatment CRP expression level was higher than that in the control group; and 4) the post-treatment CRP expression level was significantly lower than the pretreatment one (All P-values< 0.05). Based upon the efficacy, the observation group was divided into an effective group and an invalid group. The post-treatment expression levels of PLT and CRP in the effective group were lower than those in the invalid group (P< 0.05). Based upon the ROC curve, the area under curves (AUC) of PLT, CRP, and joint detection were 0.843, 0.864, and 0.886, respectively. When the cut-off point was > 0.579, the best specificity and sensitivity were 98.44 and 70.59%, respectively. According to the Pearson test, positive correlations existed between PLT and CRP, between PLT and PSI scores, and between CRP and PSI scores. In conclusion, the expression levels of PLT and CRP in severely pneumonic patients might be used to evaluate the efficacy and conducive to detection of the disease, which have high application values in clinic.